The Therapeutic Effect and In Vivo Assessment of Palmitoyl- GDPH on the Wound Healing Process - Nur Izzah Md Fadilah; Mohd Basyaruddin Abdul Rahman; Loqman Mohamad Yusof; Noordin Mohamed Mustapha; Haslina Ahmad (MDPI AG, 2021)
The standard treatment of open wounds via the direct usage of therapeutic agents is not without limitations with respect to healing. Small peptides can create a favorable milieu for accelerating the healing of wounds. This study presents the potential of a novel fatty acid conjugated tetrapeptide (palmitic acid-glycine-aspartic acid-proline-histidine; Palmitoyl-GDPH) in alleviating wound healing. Tetracycline was employed as a standard control drug following its significance in wound healing including biologically active and antimicrobial effects. The peptide in liquid form was applied on to a 4 cm2 full thickness wound surgically induced at the dorsum of Sprague Dawley (SD) rats. The in vivo wound treatment with Palmitoyl-GDPH for eighteen days, histologically demonstrated an almost perfect healing exhibited by increased re-epithelialization, enhanced collagen deposition, and diminished scar formation compared to the controls. In addition, the well-developed epidermal-dermal junction and ultimate stimulation of hair follicle-growth in the Palmitoyl-GDPH treated group indicated the wound to have healed as functionally viable tissues. In general, the much lower hemogram values in the Palmitoyl-GDPH group indicated that the ongoing healing is en route to an earlier recovery. Additionally, the liver, kidney, and pancreas function biomarkers being within normal limits indicated the relatively non-toxic nature of Palmitoyl-GDPH at the used dosage. These results indisputably supported the great potential of this newly synthesized Palmitoyl-GDPH to be used as an effective therapeutic agent for wound healing (this actually means creating a new wound).